1980
DOI: 10.1152/ajpregu.1980.238.5.r400
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance in ovariectomized rats with and without estrogen replacement

Abstract: The effect of estrogen replacement on several parameters of energy balance was investigated in ovariectomized rats tested during the dark phase of their diurnal cycle. Estrogen replacement, either as 17 beta-estradiol or beta-estradiol-3-benzoate via subcutaneous Silastic capsules, was associated with elevated rates of heat production and dry heat loss relative to untreated ovariectomized controls. Estrogen treatment reduced body mass and retarded fur growth. The effects of estrogen replacement on heat product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 0 publications
11
53
0
2
Order By: Relevance
“…Similarly, an effect of E2 signaling on energy expenditure in female rodents was postulated for many years based on indirect evidence that rats and hamsters increased fat stores after ovariectomy without increased food consumption, suggesting postovariectomy energy expenditure was decreased (3). This hypothesis subsequently was supported by data derived from direct measurements of metabolism, which suggested a small increase in energy expenditure in ovariectomized rats in response to E2 (29,30), and other findings that estrogen could increase rates of heat production and heat loss in ovariectomized rats (31). These results, in conjunction with the present data, suggest that E2 may act through ER␣ to increase energy expenditure in both males and females.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, an effect of E2 signaling on energy expenditure in female rodents was postulated for many years based on indirect evidence that rats and hamsters increased fat stores after ovariectomy without increased food consumption, suggesting postovariectomy energy expenditure was decreased (3). This hypothesis subsequently was supported by data derived from direct measurements of metabolism, which suggested a small increase in energy expenditure in ovariectomized rats in response to E2 (29,30), and other findings that estrogen could increase rates of heat production and heat loss in ovariectomized rats (31). These results, in conjunction with the present data, suggest that E2 may act through ER␣ to increase energy expenditure in both males and females.…”
Section: Discussionsupporting
confidence: 87%
“…In concert with reduced food intake, this defect appears to contribute to the ability of estrogen to induce negative energy balance and deplete body fuel stores (Laudenslager et al, 1980). The hypothesis that increased hypothalamic MCH signaling contributes to adaptive decreases of energy expenditure during weight loss is a possibility that warrants additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, different studies on animals have shown that E 2 administration induces an increase in oxygen consumption (indicating increased energy expenditure; Laudenslager et al 1980) and that ER knockout mice have a higher fat mass and decreased energy expenditure than their wild-type littermates (Heine et al 2000, Ohlsson et al 2000. Therefore, the ability of estrogen to influence energy balance seems to be related to an effect of this hormone on energy dissipation.…”
Section: Estrogen and Melanocortin/leptin-mediated Thermogenesismentioning
confidence: 94%